2002
DOI: 10.1021/ja012691k
|View full text |Cite
|
Sign up to set email alerts
|

First Gas-Phase Detection of Dimethylstannylene and Time-Resolved Study of Some of Its Reactions

Abstract: Using a laser flash photolysis/laser probe technique, we report the observation of strong absorption signals in the wavelength region 450-520 nm (highest intensity at 514.5 nm) from four potential precursors of dimethylstannylene, SnMe(2), subjected to 193 nm UV pulses. From GC analyses of the gaseous products, combined with quantum chemical excited state CIS and TD calculations, we can attribute these absorptions largely to SnMe(2), with SnMe(4) as the cleanest source of the species. Kinetic studies have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
31
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 67 publications
8
31
0
Order By: Relevance
“…This computational result is consistent with the experimental observation that Me 2 Sn is unreactive towards C À H bonds. [8] Likewise, my theoretical findings also suggest that Me 2 Ge does not insert readily into the CÀH bond, which has been confirmed by experimental works. [20] Silane insertion reactions: The geometrical results from the theoretical study on silane insertion reactions [Eq.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…This computational result is consistent with the experimental observation that Me 2 Sn is unreactive towards C À H bonds. [8] Likewise, my theoretical findings also suggest that Me 2 Ge does not insert readily into the CÀH bond, which has been confirmed by experimental works. [20] Silane insertion reactions: The geometrical results from the theoretical study on silane insertion reactions [Eq.…”
supporting
confidence: 74%
“…The principal motivation for this research was a remarkable recent experimental discovery by Walsh et al [8] who, using a laser flash photolysis/laser probe technique, showed that Me 2 Sn does not insert readily into CÀH, SiÀH, GeÀH, CÀC, SiÀC, or GeÀC bonds. It is also unreactive towards alkenes, although not towards dienes or alkynes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations